2009
DOI: 10.1142/s0218625x09012512
|View full text |Cite
|
Sign up to set email alerts
|

Laser Cladding of Magnesium Alloy Az91d With Silicon Carbide

Abstract: Mg alloys are ultralight but their structural applications are often limited by their poor wear and corrosion resistance. The research aimed to address the problem by laser-cladding. Cladding with SiC powder onto surface of AZ91D was carried out using Nd :YAG laser. The laser-clad surface was analyzed using the optical microscope, SEM equipped with EDS, and XRD and found to contain SiC and other Si compounds such as Mg 2 Si and Al 3.21 Si 0.47 as well as much refined α- Mg grains and β- Mg 17 Al 12 intermetall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Mg alloys are important engineering materials, and they are widely used in the automobile, communication and aerospace fields due to low density and high specific strength [7][8][9][10]. In order to improve their poor surface-related properties, many experiments have been performed to demonstrate that laser surface treatment can be used to further extend the application of Mg alloy [11][12][13][14][15]. Here we present our work on darkening surface of AZ31B Mg alloy induced by nanosecond pulse Nd:YAG laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Mg alloys are important engineering materials, and they are widely used in the automobile, communication and aerospace fields due to low density and high specific strength [7][8][9][10]. In order to improve their poor surface-related properties, many experiments have been performed to demonstrate that laser surface treatment can be used to further extend the application of Mg alloy [11][12][13][14][15]. Here we present our work on darkening surface of AZ31B Mg alloy induced by nanosecond pulse Nd:YAG laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort has been made in the past decade or so to study casting [1,2,3], welding [4], machining [5,6], heat treatment [7,8], phase transformation [9], surface coating [10,11], and laser processing [11,12,13,14,15,16] of various magnesium alloys, including AM50A [5,17], AM60 [1], AZ31B [18], AZ91D [4,7,8,9,10,11,12,13,14,15,16], and Mg-based composites [19,20]. Effort has also been made to study the materials' corrosion mechanisms [7,18,20,21,22,23], biocorrosion behavior [8,13], wear resistance [24], fatigue properties [25] and fracture under dynamic loading [17].…”
Section: Introductionmentioning
confidence: 99%
“…Laser surface engineering can be used to enhance surface-related properties of metallic alloys without affecting the bulk properties. Previous studies have shown that corrosion and wear resistance of Mg alloy can be improved significantly after laser surface treatment [5][6][7][8][9]. However, not much has been understood on the relationship between laser-Mg alloy interaction and surface microstructure as well as surface properties of the irradiated area.…”
Section: Introductionmentioning
confidence: 99%